Observation of spin and valley splitting of Landau levels under magnetic tunneling in graphene/boron nitride/graphene structures - Khanin, Yu.N.; Vdovin, E.E.; Larkin, I.A.; Makarovsky, O.; Sklyueva, Yu.A.; Mishchenko, A.; Wang, Yi Bo; Kozikov, A.; Gorbachev, R.V.; Novoselov, K.S. (Springer, 2018)
Resonance magnetic tunneling in heterostructures formed by graphene single sheets separated by a hexagonal boron nitride barrier and bounded by two gates has been investigated in a strong magnetic field, which has allowed observing transitions between spin- and valley-split Landau levels with various indices belonging to different graphene sheets. An unexpected increase with the temperature in the interlayer tunneling conductance owing to transitions between the Landau levels in strong magnetic fields cannot be explained by existing theories.